Análisis diseño e implementación de un sistema web para la gestión de matrículas y seguimiento de graduados para el Colegio de Bachillerato El Oro, utilizando la metodología Iconix con el framework Django y PostgreSQL. - Calle Calle, Cristhian Eduardo (2015)
College School in El Oro several problems arose in the process of enrollment, and information of graduate students, since previously the school did not have a computer system that automates these processes. One of the main problems was too much time spent performing the enrollment process and the delay in complying with requests for information from students for internal departments and the District of Education; in these circumstances the idea to analyze, design and implement a Web System for enrollment management and monitoring graduates College School El Oro, it allows students together with the administrative staff of the College perform processes graduate enrollment and monitoring; the system also bases its work on a web environment for ease of connection and work. As development tools Django Web Framework is open source and written in Python was used; it allows web applications quickly and with less code; Being the handling and manipulation of large amounts of information more or less two thousand records concluded that use PostgreSQL is a management system database free and very powerful code. For the Iconix system development methodology, which is a methodology that lies between the speed of XP and complexity of RUP, Iconix is ​​a simplified process of traditional processes and adapts well to the rapid development with Django was used. Therefore the system allows the control and management of enrollment management and monitoring graduates perform optimally and efficiently, which Agilita work giving users better service and contributing to technological development